2022
DOI: 10.1016/j.ajpath.2022.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Signals of Significantly Increased Vaccine Breakthrough, Decreased Hospitalization Rates, and Less Severe Disease in Patients with Coronavirus Disease 2019 Caused by the Omicron Variant of Severe Acute Respiratory Syndrome Coronavirus 2 in Houston, Texas

Abstract: Genetic variants of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) continue to dramatically alter the landscape of the coronavirus disease 2019 (COVID-19) pandemic. The recently described variant of concern designated Omicron Q5 (B.1.1.529) has rapidly spread worldwide and is now responsible for the majority of COVID-19 cases in many countries. Because Omicron was recognized recently, many knowledge gaps exist about its epidemiology, clinical severity, and disease course. A genome sequencing stud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
169
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(199 citation statements)
references
References 62 publications
18
169
1
Order By: Relevance
“…Evidence from in vitro studies in sera from vaccinated subjects has shown a 3 to 15-fold, 1.4 to 3-fold and 25- to 40-fold reduction in neutralizing activity of antibodies for the Beta, Delta and Omicron variants respectively in comparison to earlier variants of SARS-CoV-2 [ [16] , [17] , [18] , [19] , [20] , [21] , [22] ]. These results are generally consistent with data from epidemiologic studies suggesting that the probability of breakthrough infections increases with the Omicron variant than Delta or Alpha variants [ 23 ]. Other virologic characteristics such as the increased viral load, the shorter incubation chronic periods, the reduction of the time of immune memory to respond effectively, and the increased fusogenicity of the SARS-CoV-2 spike protein observed in the Delta variant may ease fusion of the virus and increase its propagation, resulting in decreased effectiveness of humoral immunity [ 24 ].…”
Section: What Are the Causes Of Breakthrough Infections?supporting
confidence: 89%
See 1 more Smart Citation
“…Evidence from in vitro studies in sera from vaccinated subjects has shown a 3 to 15-fold, 1.4 to 3-fold and 25- to 40-fold reduction in neutralizing activity of antibodies for the Beta, Delta and Omicron variants respectively in comparison to earlier variants of SARS-CoV-2 [ [16] , [17] , [18] , [19] , [20] , [21] , [22] ]. These results are generally consistent with data from epidemiologic studies suggesting that the probability of breakthrough infections increases with the Omicron variant than Delta or Alpha variants [ 23 ]. Other virologic characteristics such as the increased viral load, the shorter incubation chronic periods, the reduction of the time of immune memory to respond effectively, and the increased fusogenicity of the SARS-CoV-2 spike protein observed in the Delta variant may ease fusion of the virus and increase its propagation, resulting in decreased effectiveness of humoral immunity [ 24 ].…”
Section: What Are the Causes Of Breakthrough Infections?supporting
confidence: 89%
“…Given that there is a parallel trend regarding neutralizing antibody titers [ 35 ], which may serve as a surrogate of immunity against SARS-CoV-2 [ 37 ], this humoral phenomenon coincides with a gradually increasing susceptibility of fully vaccinated individuals for breakthrough infections in the months following immunization [ [38] , [39] , [40] , [41] ]. As immunity diminishes over time, the most notable decreases in vaccine effectiveness have occurred in milder forms and asymptomatic infections, in those vaccinated earliest, in older subjects and in those infected with the Omicron variant [ 15 , 23 ]. Therefore, there is an urgent need to examine the effectiveness of both prior SARS-CoV-2 infection and vaccination against the Omicron variant.…”
Section: What Are the Causes Of Breakthrough Infections?mentioning
confidence: 99%
“…Our findings suggest that almost a quarter of patients with a COVID-19 diagnosis had symptoms severe enough for them to be bedridden for 7 days or longer, which was associated with persistent long-term mental health symptoms. 35 Our study participants were diagnosed with COVID-19 from February, 2020, to August, 2021; therefore, with the advent of vaccinations and new, reportedly weaker SARS-CoV-2 variants, 35 the proportion of patients with COVID-19 with a severe course of acute illness might be lower in more recently infected individuals.…”
Section: Discussionmentioning
confidence: 97%
“…Due to the unique H69/V70 deletion in the spike gene, the analysis of Omicron sequences would show S ‐gene target failure (SGTF), which helps to diagnose Omicron accurately. However, compared to BA.1, sublineage BA.2 lacks such deletion, resulting in not being detected by SGTF 138 …”
Section: Strategies Against the Omicron Variantmentioning
confidence: 99%
“…However, compared to BA.1, sublineage BA.2 lacks such deletion, resulting in not being detected by SGTF. 138 Population‐level protection against SARS‐CoV‐2 (and their variants) can also be monitored by regular antibody testing, either through traditional enzyme‐linked immunosorbent assays or through rapid lateral flow‐based neutralizing antibody tests. Such monitoring, at least in the short term during large‐scale outbreaks, can guide decisions and policies regarding vaccination schedules.…”
Section: Strategies Against the Omicron Variantmentioning
confidence: 99%